Maintenance Green Wall In Smart Parking Building Ministry Of Public Of Works Of Housing, Jakarta - Yunita Dian Suwandari; Mirnayani Mirnayani (Faculty of Engineering, Malikussaleh University, 2018)
Implementation of sustainable building is currently a top priority of the government, based on the government's determination to reduce CO2 emissions to 26% - 41% by the end of 2020. The use of green wall technology in Green building is now one of the characteristics of buildings with green concept. However, maintenance issues, especially in its design are very seldom explored whereas this is important to achieve the purpose of building efficient and sustainable. This study aims to examine how the application of green wall in buildings that have a Green certificate and problems that occur on the application of green wall technology and what solutions can be taken to overcome them. The methodology used is qualitative in combination with case studies and review literature. The result of this research is to give a picture of green wall maintenance in green building in Indonesia.